PENERAPAN MODEL JIGSAW II UNTUK PENINGKATAN KEMAMPUAN MENGANALISIS TEKS LAPORAN HASIL OBSERVASI DI SMK - Rusmini, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study purposes to describe proses and result of the ability learning of analyting the text of the report on the observation through cooperative learning model Jigsaw II type and scientific approach inthe first grade students of Vocational School 1 Mempawah Hilir in accounting program 2. The data  used in this study was obtained from the action planning, implementation, observation, and reflection on the ability learning of analyzing the text of the report on the observation. The data source are 37 studens of the first grade of vocational school I Mempawah Hilir in accounting program 2, teacher/writer and obsever. Data collection techniques is direct observation, measurement value of the ability  learning of analyzing the text of the report on the observation and documentation study. Based on the results of this study concluded that cooperative learning model Jigsaw II can improve the ability to analyze text  of the report on the observation. This success is supported by student interest in the form of response is very active, active, fairly active, inactive, and inactive cycle I, II, and III have enhancement significantly.  Results of learning to analyze texts observation reports also increased. The average class of  cycle I of 66,6 with a level of completeness of 32,4% to 73,3 with a level of completeness 56,8% in the cycle II, and the average class of cycle III of 81,5 with a level of completeness of 83,8%.Keywords: The Text of The Report on The Observation, Cooperative Learning Model Jigsaw II Type